Pembentukan Karakter Sopan Santun Siswa Sekolah Dasar Melalui Budaya Jaga Regol - Allinda Hamidah; Andina Nuril Kholifah (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2021)
The objectives of this study were to: (1) describe the implementation of Jaga Regol cultural preservation at MI Thoriqotul Hidayah Gelap, (2) describe the impact of preserving Jaga Regol culture in shaping the character of courtesy of students at MI Thoriqotul Hidayah Gelap To achieve the above objectives, a qualitative approach is used. The data collection technique was done by means of observation, interviews, and documentation. Data analysis begins with pre-field analysis, analysis during the field, questions and data validity which includes credibility tests, triangulation methods and confirmability testing. The results showed that: (1) the implementation of cultural preservation of Jaga Regol in shaping courtesy in schools with routine school habits which are held every day starting from activities before starting learning and activities while in the learning process. (2) the impactof the implementation of handshake culture preservation in shaping the character of courtesy in schools, namely the implementation of character education in schools, including speaking friendly to others (principals, teachers, employees), not chatting when the teacher explains the material, not mocking other friends, Second , the implementation of character education outside of school is divided into 2, namely in the family and society, including: (a) in the family: saying greetings when going out or entering the house, respecting the opinions of family members, helping with household chores, (b) in the community: not spitting in any place, cooperating with each other, not interrupting other people's conversations